Epidemiology of biliary atresia in England and Wales (1999–2006). Issue 6 (19th May 2009) - Livesey, E; Borja, M Cortina; Sharif, K; Alizai, N; McClean, P; Kelly, D; Hadzic, N; Davenport, M
Abstract : Objective: To identify the epidemiological characteristics of infants with biliary atresia in England and Wales, since centralisation of its management in 1999. Methods: The care of infants with biliary atresia (BA) in England and Wales is centralised to only three centres. All infants (treated from January 1999 to December 2006) were identified from a prospective national database; demographic details were ascertained from medical records and compared between two groups based on presumed aetiology (isolated biliary atresia (IBA) and developmental biliary atresia (DBA) (for example, syndromic infants, biliary atresia splenic malformation, cystic biliary atresia)). Results: There were 302 (133 male (44%)) infants with BA that could be divided into IBA (n = 219, 73%) and DBA (n = 76, 25%). The overall incidence was 0.58/10 000 (1 in 17 049) live births with marked regional differences along a north-west/south-east axis varying from 0.38 (north-west England) to 0.78 (south-east England)/10 000 live births (OR 2.05 (95% CI 1.26–3.41); p = 0.002). The commonest month of birth was September with December being the least common, although there was no evidence for significant seasonal variation (p = 0.2). Infants with DBA were more likely to be female (p<0.001), of white background (p = 0.01), first-born (p = 0.04) and to be formula-fed (p = 0.07). Infants of south Asian origin came to surgery at an older age (59 (IQ 45–75) versus 52 (IQ 42–65) days; p = 0.03). Conclusions: There is a remarkable variation of incidence of biliary atresia within England and Wales, some of which may have been caused by factors related to a different aetiological and racial background.